2011
DOI: 10.1021/bi101731d
|View full text |Cite
|
Sign up to set email alerts
|

Biflavonoids Are Superior to Monoflavonoids in Inhibiting Amyloid-β Toxicity and Fibrillogenesis via Accumulation of Nontoxic Oligomer-like Structures

Abstract: Polymerization of monomeric amyloid-β peptides (Aβ) into soluble oligomers and insoluble fibrils is one of the major pathways triggering the pathogenesis of Alzheimer's disease (AD). Using small molecules to prevent the polymerization of Aβ peptides can, therefore, be an effective therapeutic strategy for AD. In this study, we investigate the effects of mono- and biflavonoids in Aβ42-induced toxicity and fibrillogenesis and find that the biflavonoid taiwaniaflavone (TF) effectively and specifically inhibits Aβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
99
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 41 publications
15
99
1
Order By: Relevance
“…Recent studies have been devoted toward the design of antibodies (Hillen et al, 2010), peptides (Esteras-Chopo et al, 2008), flavonoids (Thapa et al, 2011), or other pharmaceutical compounds ) to block A␤ peptide oligomerization, but the in vivo efficiency of such a strategy requires extensive knowledge of the oligomerization process and the toxicity of the various oligomeric forms. Other studies have focused on the functional interactions between A␤ peptide and glutamate receptors (Decker et al, 2010b;Hu et al, 2009;Texidó et al, 2011;Zhao et al, 2010) or have attempted to reinforce neuronal defenses through the neurotrophic effects of growth factors or membrane lipids such as docosahexaenoic acid (Ma et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have been devoted toward the design of antibodies (Hillen et al, 2010), peptides (Esteras-Chopo et al, 2008), flavonoids (Thapa et al, 2011), or other pharmaceutical compounds ) to block A␤ peptide oligomerization, but the in vivo efficiency of such a strategy requires extensive knowledge of the oligomerization process and the toxicity of the various oligomeric forms. Other studies have focused on the functional interactions between A␤ peptide and glutamate receptors (Decker et al, 2010b;Hu et al, 2009;Texidó et al, 2011;Zhao et al, 2010) or have attempted to reinforce neuronal defenses through the neurotrophic effects of growth factors or membrane lipids such as docosahexaenoic acid (Ma et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…3.2). Thus, the biflavonoid was found to be more effective at reducing A" fibril extension compared to the monoflavonoid (Thapa et al 2011). …”
Section: Biflavonoids As A" Aggregation Inhibitorsmentioning
confidence: 94%
“…The polyphenol that contains both ferulic acid and styryl benzene has been shown to be more effective than either of the two individual compounds . It has been further suggested that the dimers of A" binding monoflavonoids, separated by an appropriate size linker, may serve as a general structure for inhibitors of A" aggregation and toxicity (Thapa et al 2011). Such biflavonoid compounds may be promising therapeutic candidates for AD.…”
Section: Beneficial Roles Of Naturally Occurring Polyphenolic Compounmentioning
confidence: 99%
See 1 more Smart Citation
“…Using small molecules to prevent the aggregation of Aβ is an effective therapeutic strategy for AD. Monoflavonoids and biflavonoids were reported as Aβ aggregation inhibitors and cyto-protectors 2 . But the mechanism of action remains unknown.…”
Section: Resultsmentioning
confidence: 99%